A Key Station Identification Method for Urban Rail Transit: A Case Study of Beijing Subway - Sun, Shiwei; Li, Haiying; Xu, Xinyue (Promet - Traffic&Transportation, 2017)
Congestion occurs and propagates in the stations of urban rail transit, which results in the impendent need to comprehensively evaluate the station performance. Based on complex network theory, a key station identification method is considered. This approach considers both the topology and dynamic operation states of urban rail transit network, such as degree, passenger demand, system capacity and capacity utilization. A case of Beijing urban rail transit is applied to verify the validation of the proposed method. It shows that the method can be helpful to daily passenger flow control and capacity enhancement during peak hours.